“Would you accept having your DNA profile inserted in the National Forensic DNA database? Why?” Results of a questionnaire applied in Portugal - Machado, Helena (2014)
The creation and expansion of forensic DNA databases might involve potential threats to the protection of a range of human rights. At the same time, such databases have social benefits. Based on data collected through an online questionnaire applied to 628 individuals in Portugal, this paper aims to analyze the citizens’ willingness to donate voluntarily a sample for profiling and inclusion in the National Forensic DNA Database and the views underpinning such a decision. Nearly one-quarter of the respondents would indicate ‘no’, and this negative response increased significantly with age and education. The overriding willingness to accept the inclusion of the individual genetic profile indicates an acknowledgement of the investigative potential of forensic DNA technologies and a relegation of civil liberties and human rights to the background, owing to the perceived benefits of protecting both society and the individual from crime. This rationale is mostly expressed by the idea that all citizens should contribute to the expansion of the National Forensic DNA Database for reasons that range from the more abstract assumption that donating a sample for profiling would be helpful in fighting crime to the more concrete suggestion that everyone (criminals and non-criminals) should be in the database. The concerns with the risks of accepting the donation of a sample for genetic profiling and inclusion in the National Forensic DNA Database are mostly related to lack of control and insufficient or unclear regulations concerning safeguarding individuals’ data and supervising the access and uses of genetic data. By providing an empirically-grounded understanding of the attitudes regarding willingness to donate voluntary a sample for profiling and inclusion in a National Forensic DNA Database, this study also considers the citizens’ perceived benefits and risks of operating forensic DNA databases. These collective views might be useful for the formation of international common ethical standards for the development and governance of DNA databases in a framework in which the citizens’ perspectives are taken into consideration.